The Integration of Islamic Educational Values in Ibn Arabi's Sufi Theory for Shaping Islamic Character - Haris, Abdul; Nasri, Ulyan (Jurnal Ilmiah Profesi Pendidikan, 2024)
The urgency of this study lies in the profound need to integrate Islamic educational values into Ibn Arabi's Sufi theory as a spiritual approach to shaping Islamic character. Ibn Arabi's Sufi theory offers a rich perspective on existential unity and spiritual purification, which is relevant for building character based on Islamic values. This study aims to analyze how Ibn Arabi's Sufi theory can be adapted and integrated into Islamic education concepts, particularly in shaping Islamic character that reflects noble morals. The research method employed is library research, with data collection conducted through a literature review of Ibn Arabi’s primary works and various references related to Islamic education. The data analysis technique is descriptive-analytical to explore the relevance of Ibn Arabi’s Sufi theory to Islamic educational values. The results indicate that key concepts in Ibn Arabi's theory, such as wahdat al-wujud, maqamat, and ahwal, provide a strong philosophical foundation for spiritual education. Integrating these values can create a holistic approach to Islamic education, emphasizing spiritual dimensions alongside cognitive and affective aspects.  In conclusion, Ibn Arabi's Sufi theory is relevant as a foundation for Islamic education that not only builds knowledge but also shapes Islamic character. The implications of this study can be used to design a more comprehensive Islamic education curriculum, emphasizing the spiritual development of students.